Analisis Kepecayaan Diri Pada Mahasiswa Unimal - Mulyana Mulyana (Jurnal Psikologi Terapan, 2019)
This study aims to determine student confidence in reality. The research subjects were 93 students consisting of 89 male students and 4 female students. The age range of respondents is 17 to 22 years. Based on psychometric tests conducted through internal consistency and construct validity test, the scale of student self-confidence has less validity and reliability, no validity and no reliability. This measure of self-confidence is due to having Cronbarch's alpha 0.493 while a good measuring instrument must have cronbarch's alpha 0.7 to 0.9. This scale cannot measure the same contract consistently, cannot distinguish individuals with high and low self-esteem, and is invalid for measuring thanksgiving through four factors, namely believing in one's own abilities, acting independently in making decisions, having a positive sense against yourself, and dare to express opinions. With good psychometric standards, the self-confidence scale described and presented in this study cannot be used to  measure  self-confidence  in  the  context  of  research and  clinical  intervention  in  the  student population